2010
DOI: 10.1038/cdd.2010.149
|View full text |Cite
|
Sign up to set email alerts
|

HDLs inhibit endoplasmic reticulum stress and autophagic response induced by oxidized LDLs

Abstract: The apoptotic effect of oxidized LDLs (oxLDLs) is mediated through a complex sequence of signaling events involving a deregulation of the cytosolic Ca 2 þ homeostasis. OxLDLs also trigger ER stress that may lead to cellular dysfunction and apoptosis, through the activation of the IRE1a/c-Jun N-terminal kinase pathway. Moreover, ER stress and oxidized lipids have been shown to trigger autophagy. The antiatherogenic high-density lipoproteins (HDLs) display protective effects against oxLDLs toxicity. To more deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 40 publications
(69 reference statements)
4
89
0
Order By: Relevance
“…HDL and its subfractions offer important cytoprotection for endothelial cells in response to different proapoptotic stimuli. Attenuation of endothelial cell apoptosis by HDL involves inhibition of death receptor, mitochondrial, and endoplasmic reticulum signaling pathways (93)(94)(95)(96). Tumor necrosis factor ␣-induced apoptosis via death-receptor signaling is blocked by HDL via inhibition of CPP32-like protease activity (97 ).…”
Section: Antiapoptotic Effectsmentioning
confidence: 99%
“…HDL and its subfractions offer important cytoprotection for endothelial cells in response to different proapoptotic stimuli. Attenuation of endothelial cell apoptosis by HDL involves inhibition of death receptor, mitochondrial, and endoplasmic reticulum signaling pathways (93)(94)(95)(96). Tumor necrosis factor ␣-induced apoptosis via death-receptor signaling is blocked by HDL via inhibition of CPP32-like protease activity (97 ).…”
Section: Antiapoptotic Effectsmentioning
confidence: 99%
“…These initial observations have been extended and lipophagy now appears to be important in maintaining lipid homeostasis in a diverse set of cell types from neurons to fibroblasts (Singh et al, 2009;Liu & Czaja, 2013;Settembre & Ballabio, 2014). Here, we demonstrate an important role for endothelial autophagy in maintaining vascular lipid homeostasis.It has been previously observed that when endothelial cells in culture are exposed to OxLDL they respond with an increase in autophagosomes (Nowicki et al, 2007;Zhang et al, 2010;Muller et al, 2011;Menghini et al, 2014). In general, autophagic flux can be assessed by simultaneously analyzing the levels of LC3-II, which labels autophagosome membranes, and measuring the levels of p62, a protein cleared via autophagic degradation.…”
mentioning
confidence: 99%
“…It has been previously observed that when endothelial cells in culture are exposed to OxLDL they respond with an increase in autophagosomes (Nowicki et al, 2007;Zhang et al, 2010;Muller et al, 2011;Menghini et al, 2014). In general, autophagic flux can be assessed by simultaneously analyzing the levels of LC3-II, which labels autophagosome membranes, and measuring the levels of p62, a protein cleared via autophagic degradation.…”
mentioning
confidence: 99%
“…It is well-known that autophagy occurs in advanced atherosclerotic plaques (4)(5)(6), and that macrophage autophagy exerts a protective effect in advanced atherosclerosis (7). Previous studies have shown that ox-LDL may induce autophagy in endothelial cells, leading to the degradation of ox-LDL through autolysosomes (8,9). However, little is currently known about whether ox-LDL may induce autophagy in macrophages.…”
Section: Introductionmentioning
confidence: 98%